How do you simplify (1- i ) - ( 3- 1) ( 3+ 1)?

1 Answer
Oct 4, 2017

(1-i)-(3-1)(3+1)=-7

Explanation:

The P in PEMDAS stands for parentheses, so do what you can in parentheses first:
You can't simplify (1-i) since i isn't a real number.
3-1=2, and 3+1=4, so we can rewrite the expression:
(1-i)-(3-1)(3+1)=(1-i)-(2)(4)
Multiplication and Division come before addition and subtraction in the order of operations, so multiply 2*4=8.
Now the expression is (1-i)-8. Again, we can't combine that i with a real number, but we know that 1-8=-7. So our final result is
(1-i)-8=1-i-8=-7-i